Hubungan Penerapan Aspek K3 Terhadap Hasil Belajar Siswa Kelas XI Teknik Pengelasan Pada Mata Pelajaran Las Busur Manual (SMAW) di SMK N 1 Guguk - Andre Maryonda; Nelvi Erizon; Irzal Irzal; Hendri Nurdin (Jurnal Vokasi Mekanika (VoMek), 2025)
The following study is intended to find if it exists an association among these application about K3 aspects along with student learning outcomes of the welding engineering workshop at SMK Negeri 1 Guguk. During the practice, it was found that there was a lack of understanding and implementation of K3 aspects by the Welding Technology students, as well as insufficient attention to and maintenance of K3 equipment. This research applies correlational methods with quantitative techniques. A total of 55 class XI TLAS students in the SMAW Welding Engineering subject were to be used as subjects. Sampling method adopted in this study is the purposive sampling technique. The data testing results in this study used the product-moment correlation, which showed that the calculated r score was higher than the table r value, indicating a positive relationship between the variables. The significance score was low, leading to the acceptance of the alternative hypothesis (Ha). Thus, the research hypothesis is recognized at a sufficient interpretation level. The data testing results show that the implementation of K3 aspects contributes to student learning outcomes, although the contribution is not dominant. Other aspects that influence student learning outcomes were not studied in this research. Outcome of the data examination lead to theconclusion that application about K3 aspects shows a direct impact on the results of learning of class XI Welding Engineering students in the manual arc welding subject at SMK Negeri 1 Guguk.